Eunuchs or Females? Causes and Consequences of Gynodioecy on Morphology, Ploidy, and Ecology of Stellaria graminea L. (Caryophyllaceae) - Kučera, Jaromír; Svitok, Marek; Gbúrová Štubňová, Eliška; Mártonfiová, Lenka; Lafon Placette, Clément; Slovák, Marek (Frontiers in Plant Science, 2021)
Plant speciation results from intricate processes such as polyploidization, reproductive strategy shifts and adaptation. These evolutionary processes often co-occur, blurring their respective contributions and interactions in the speciation continuum. Here, relying on a large-scale study, we tested whether gynodioecy triggers the divergent evolution of flower morphology and genome between sexes, and contributes to the establishment of polyploids and colonization of ecological niches in Stellaria graminea. We found that gynodioecy in S. graminea leads to flower morphology divergence between females and hermaphrodites, likely due to sexual selection. Contrary to our expectations, gynodioecy occurs evenly in diploids and tetraploids, suggesting that this reproductive strategy was not involved in the establishment of polyploids. Both diploid and tetraploid females have a larger genome size than hermaphrodites, suggesting the presence of sex chromosomes. Finally, ecology differs between cytotypes and to a lesser extent between sexes, suggesting that the link between environment and presence of females is indirect and likely explained by other aspects of the species’ life history. Our study shows that gynodioecy leads to the consistent evolution of sexual traits across a wide range of populations, cytotypes and environments within a given species, and this likely contributes to the phenotypic and genetic distinctiveness of the species from its sister clades.